Luto Infantil - Roncatto, Rafaela (My University, 2019)
The general objective of this research was to identify possible interventions of the psychologist in the elaboration of mourning with the death of one of the parents in childhood. The study was delineated from a qualitative, bibliographic research of an exploratory nature. The data collection was done through books, articles, theses and dissertations where the instrument used to collect the data was the note sheet, and the integrative synthesis was adopted as a reference for analysis. For the bibliographical research, it was initially carried out the reading and selection of articles with the themes: mourning, infant mourning, childhood, child development and parental mourning. The results pointed to the importance of understanding and respecting the child's cognitive understanding of grief as well as coping strategies according to maturative aspects, causes of death and external factors related to the child, such as family reaction to the death of the parent, as well as the relationship of the child with that parent who died. It was possible to identify that the family has an important aspect to the phenomenon, since the form found by it may help the meanings attributed to mourning, as well as to support the absence of the deceased relative. From the results, it is possible to conclude that psychology can contribute to situations of child mourning, offering a space for listening and symbolizing both the children and their families (sic).
O objetivo geral desta pesquisa foi o de identificar possíveis intervenções do psicólogo na elaboração do luto com a morte de um dos genitores na infância. O estudo foi delineado a partir de uma pesquisa qualitativa, bibliográfica de caráter exploratório. A coleta de dados se deu por meio de livros, artigos, teses e dissertações onde o instrumento utilizado para a coleta dos dados foi a ficha de apontamentos, sendo a síntese integradora adotada como referencial de análise. Para a pesquisa bibliográfica, inicialmente foi realizada a leitura e seleção de artigos com os temas: luto, luto infantil, infância, desenvolvimento infantil e luto parental. Os resultados apontaram para a importância de compreender e respeitar a compreensão cognitiva da criança sobre o luto, bem como as estratégias de enfrentamento de acordo com os aspectos maturativos, as causas da morte e os fatores externos relacionadas à criança, como a reação da família frente à morte do genitor, bem como a relação da criança com aquele genitor que morreu. Foi possível identificar que a família tem um aspecto importante para o fenômeno, uma vez que a forma por ela encontrada poderá auxiliar para os significados atribuídos ao luto, assim como, para suportar a ausência do familiar falecido. A partir dos resultados, é possível concluir que a psicologia pode contribuir em situações do luto infantil, oferecendo um espaço de escuta e simbolização tanto com as crianças como com os seus familiares (sic).
Keywords: Infância; Morte; Luto em crianças; Luto - Aspectos psicológicos